Hubungan Antara Dukungan Sosial dengan Kualitas Hidup pada Lansia di Rumah Pelayanan Sosial Semarang - Rakhma Mayangsari; Iskim Luthfa; Moch. Aspihan (Pusat Riset dan Inovasi Nasional, 2026)
Background: Elderly people were a vulnerable population who experienced physical, psychological, social, and environmental changes that could reduce their quality of life. One important factor influencing quality of life was social support. Social support played a crucial role in helping alderly people improve their well-being and life satisfaction. Elderly people who received high social support from family, friends, or their environment tended to feel more valued, loved, and cared for. Method: This study employed a quantitative method with a cross-sectional approach. The study population consisted of 204 elderly people living in Pucang Gading Social Service Home, Semarang and Wening Wardoyo Social Servise Home, Ungaran. A total of 135 respondents were selection using non probability sampling. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS) to measure social support and the WHOQOL-OLD questionnaire to assess quality of life of older adults. Data analysis was conducted using the Somers’d test with a significance level of 0,05. Results: The results showed that most respondents have high social support (60,7%) and high quality of life (74,1%). The somers’d test indicated a p-value = 0,000 (p<0,05) and a correlation coefficient (r) of 0,508, indicating a positive relationship with moderate strength. Conclusion: There was a significant relationship between social support and quality of life among elderly people at social homes in Semarang. Increasing social support from family, peers, and the institutional environment could help elderly people experience their later years more happily, meaningfully, and prosperously.